1991
DOI: 10.1161/01.str.22.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Lithium ion does not protect brain against transient ischemia in gerbils.

Abstract: It has been proposed that lithium ion desensitizes neuronal receptors that function via the inositol phospholipid signaling mechanism. We examined the effects of lithium chloride on the morphologic outcome after 5 minutes of cerebral ischemia induced in gerbils by occluding both common carotid arteries under brief halothane anesthesia. In three treated groups of 10 gerbils each, 5 meq/kg i.p. lithium chloride was given 2 days, 1 day, and 2 hours before ischemia; 2 hours before ischemia; or immediately after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Two-day pretreatment with lithium was reported not to protect brain tissue against transient ischemia in gerbils (Yoshida et al, 1991), suggesting that long-term pretreatment is a prerequisite for lithium’s protective effects. However, post-insult treatment with therapeutic doses of lithium (~1.0 mEq/kg of body weight, subcutaneously), when administered up to three hours after the onset of ischemia, also markedly decreases infarct volume and suppresses neurological deficits measured by sensory, motor, and reflex tests in a rat model of transient MCAO (Ren et al, 2003).…”
Section: Lithium In Models Of Cns Disorders and Its Clinical Implimentioning
confidence: 99%
“…Two-day pretreatment with lithium was reported not to protect brain tissue against transient ischemia in gerbils (Yoshida et al, 1991), suggesting that long-term pretreatment is a prerequisite for lithium’s protective effects. However, post-insult treatment with therapeutic doses of lithium (~1.0 mEq/kg of body weight, subcutaneously), when administered up to three hours after the onset of ischemia, also markedly decreases infarct volume and suppresses neurological deficits measured by sensory, motor, and reflex tests in a rat model of transient MCAO (Ren et al, 2003).…”
Section: Lithium In Models Of Cns Disorders and Its Clinical Implimentioning
confidence: 99%
“…For example, one report showed that lithium pretreatment at 5 mEq/kg up to two days prior to ischemia did not prevent the decrease in neuronal density in the hippocampal CA1 region of gerbils subjected to global cerebral ischemia [86] . The discrepancy could be related to the specific lithium treatment conditions and highlights the importance of optimizing dose and timing to maximize the protective effects of lithium and other drugs in stroke therapy.…”
Section: Alternate Findingsmentioning
confidence: 99%
“…During early stages of global cerebral ischemia, i.e., first 20 min of ischemia, lithium infusion at clinical equivalent doses, showed a strong edema-reducing effect when compared with ringer infusion. In the experimental setup used, this effect was nether related to blood osmolality nor hypothermia (Yoshida et al 1991), was stronger in the first 10 min of ischemia, and more evident for the dose of 10 mg·kg -1 than for 30 or 100 mg·kg -1 . The fact that lithium infusion at any concentration did not induce changes in plasma osmolality, and that the antiedema effect was more intense at the lower lithium concentration tested (10 mg·kg -1 ), strongly suggests an indirect, osmotic mechanism of action.…”
Section: Discussionmentioning
confidence: 87%
“…This complex stepwise process to develop cerebral edema begins first with the cytotoxic edema of neuroglia followed by the ionic edema of the neurons, but not the vasogenic edema, owing to the absence of reperfusion in our global brain ischemia experimental model (see Simard et al 2007;Kahle et al 2009). It has been proposed that the lithium ion desensitizes neuronal receptors that link to the inositol phospholipid signaling mechanism (Yoshida et al 1991). Lithium reduces intracellular cAMP and cGMP concentration, and decreases glutamatergic excitatory activity (Young 2009) by inhibition of NR2B tyrosine phosphorylation of NMDA receptors (Chuang 2005), increases Akt activities (Chalecka-Franaszek and Chuang 1999), cyclic AMP-response element binding protein (CREB), c-Jun-N-terminal kinase (JNK), p38 kinase (Chuang et al 2002), rescues the Wnt pathway (Cappuccio et al 2005), and attenuates interactions of Pyk2 and PSD-95 with NMDA receptor (Ma et al 2004) resulting in a lithium-induced down regulation of NMDA receptor (Ma and Zhang 2003).…”
Section: Discussionmentioning
confidence: 99%